Growth and survival of Tilapia fry (Oreochromis sp.) in different salinity concentration in experiment tank - Nurul Nassita, Lias (Universiti Malaysia Sarawak (UNIMAS), 2015)
Effect of different salinity concentration of growth and survival of Tilapia fry (Oreochromis sp.) was evaluated for a period 6 weeks in experiment tanks. Twenty (20) individual of fry were stocked in each aquarium with a mean length and weight 0.86 ± 0.08 gm and 37.42 ± 1.12 mm respectively. Fish fry were feed with commercial pellet twice a day (0800 am: 1600 pm) based on 10% of total biomass in each treatment. The basic physic-chemical water quality parameters were maintained and monitored continuously. The fish growth and survival were monitored once in fortnight. The result shows the highest weight gain was shown in T1. The highest total length gain was shown in T5. T1 shows the highest survival rate among the treatment and the highest specific growth rate (SGR) was shown in T5. The best FCR was observed in T2. However, the optimum salinity for growth and survival of fish fry is 10 ppt where the survival rate and growth rate was higher and simultaneously.